2024
DOI: 10.1113/jp285745
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide‐induced bidirectional long‐term synaptic plasticity in Drosophila mushroom body

Daichi Yamada,
Andrew M. Davidson,
Toshihide Hige

Abstract: Activation of the cAMP pathway is one of the common mechanisms underlying long‐term potentiation (LTP). In the Drosophila mushroom body, simultaneous activation of odour‐coding Kenyon cells (KCs) and reinforcement‐coding dopaminergic neurons activates adenylyl cyclase in KC presynaptic terminals, which is believed to trigger synaptic plasticity underlying olfactory associative learning. However, learning induces long‐term depression (LTD) at these synapses, contradicting the universal role of cAMP as a facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…Furthermore, a comprehensive understanding of the physiological impact of the observed structural plasticity on synaptic transmission remains elusive. Recent reports indicate that increases in cAMP levels in addition with KC activation lead to synaptic depression, with temporal differences across KC compartments ( Yamada et al 2024 ), as is the case in aversive associative learning ( Hancock et al 2022 ). The decrease in synaptic connectivity might perhaps influence the generation of learning-induced synaptic depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a comprehensive understanding of the physiological impact of the observed structural plasticity on synaptic transmission remains elusive. Recent reports indicate that increases in cAMP levels in addition with KC activation lead to synaptic depression, with temporal differences across KC compartments ( Yamada et al 2024 ), as is the case in aversive associative learning ( Hancock et al 2022 ). The decrease in synaptic connectivity might perhaps influence the generation of learning-induced synaptic depression.…”
Section: Discussionmentioning
confidence: 99%
“…The solution is twofold. First, cAMP production alone is not sufficient: A recent study showed that KCs require simultaneous cAMP production and KC depolarization in order to depress their presynaptic release probability ( Yamada et al 2024 ). Second, KCs form extensive axonal synapses with each other, as revealed in the connectome ( Eichler et al 2017 ; Takemura et al 2017 ; Li et al 2020 ).…”
Section: Stimulus-specific Neuromodulationmentioning
confidence: 99%
“…NO activates soluble guanylate cyclase (sGC), which produces cGMP and triggers transcriptional changes that promote forgetting ( Takakura et al 2023 ). sGC activity slowly potentiates KC–MBON synapses, but, as with cAMP, only when the KC is simultaneously active with sGC ( Yamada et al 2024 ).…”
Section: Stimulus-specific Neuromodulationmentioning
confidence: 99%